2014
DOI: 10.1007/s00442-014-3117-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil denitrification fluxes from three northeastern North American forests across a range of nitrogen deposition

Abstract: In northern forests, large amounts of missing N that dominate N balances at scales ranging from small watersheds to large regional drainage basins may be related to N-gas production by soil microbes. We measured denitrification rates in forest soils in northeastern North America along a N deposition gradient to determine whether N-gas fluxes were a significant fate for atmospheric N inputs and whether denitrification rates were correlated with N availability, soil O2 status, or forest type. We quantified N2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 53 publications
2
43
0
Order By: Relevance
“…A small contribution occurred after topdressing for the maize and basal fertilization for the wheat, but evident contribution was evoked after basal fertilization for the maize and topdressing for the wheat. Additionally, other studies also found the important contribution of denitrification on N 2 O emission from agriculture soil (Vilain et al, 2014), grassland (Ostrom et al, 2010;Vilain et al, 2014) and forest soil (Cheng et al, 2014;Morse et al, 2014;Vilain et al, 2014). In this study, because each fertilization event is accompanied with immediately irrigation, it is difficult to explain the above phenomena only based on the variation of soil anoxic condition caused by the soil moisture (Figs.…”
Section: Discussionmentioning
confidence: 71%
“…A small contribution occurred after topdressing for the maize and basal fertilization for the wheat, but evident contribution was evoked after basal fertilization for the maize and topdressing for the wheat. Additionally, other studies also found the important contribution of denitrification on N 2 O emission from agriculture soil (Vilain et al, 2014), grassland (Ostrom et al, 2010;Vilain et al, 2014) and forest soil (Cheng et al, 2014;Morse et al, 2014;Vilain et al, 2014). In this study, because each fertilization event is accompanied with immediately irrigation, it is difficult to explain the above phenomena only based on the variation of soil anoxic condition caused by the soil moisture (Figs.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, as the largest terrestrial biome, boreal forests lack available N because the rate of BNF is restricted by cold temperatures and low precipitation during the growing season (Alexander and Billington, 1986). Morse et al (2015) conducted field experiments in northeastern North American forests. They found that denitrification does vary coherently with patterns of N availability in forests, and there are no significant correlations between atmospheric N deposition, potential net N mineralization, and nitrification rates.…”
Section: Magnitude and Spatial Distribution Of N 2 O Emissionmentioning
confidence: 99%
“…For example, it is understood that saturation may never be achieved in well drained soils under field conditions (Wang et al, 1998). Field saturation, fs , accounts for gas filled soil pore space that may be occluded within the pore matrix at approximately the bubbling pressure (Reynolds et al, 2002) and can occur due to air encapsulation (Fayer and Hillel, 1986), fluctuating groundwater levels (Marinas et al, 2013), and biogenic gases (Morse et al, 2015).…”
Section: Introductionmentioning
confidence: 99%